Binder for high-performance PA6 / PE multi-layer co-extrusion composite film and preparation method thereof
By preparing a high-performance binder containing specific components, the problem of insufficient water resistance of PA6/PE multi-layer coextruded composite film binder is solved, and its water resistance and service life are significantly improved.
Patent Information
- Application Number
- CN202411858042.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-04
AI Technical Summary
The binder of the existing PA6/PE multi-layer coextruded composite film is insufficient in water resistance, resulting in reduced performance and shortened service life under strict operating conditions.
Using a high-performance binder, which consists of polyether diol, diphenylmethane diisocyanate, dihydroxymethylpropionic acid, 1,4-butyl glycol, dibutyltin dilaurate, silane coupling agent, triethylamine, acetone, nano calcium carbonate and vapor phase silica, is prepared by specific ratios and treatment steps to form a silane-modified polyurethane prepolymer, and additives are added to improve water resistance.
The water absorption rate of the binder is significantly reduced, its water resistance is improved, and its service life is extended, which is significantly improved compared with the prior art.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of laminating adhesives, and in particular to an adhesive for high-performance PA6 / PE multi-layer co-extruded composite films and a preparation method thereof. Background Art
[0002] PA6 / PE multi-layer co-extrusion composite film is a composite film produced by multi-layer co-extrusion technology. It is mainly composed of PA6 or nylon 6 and PE, polyethylene and other materials. The structure design of multi-layer co-extrusion composite film is flexible, and different layers can be matched and combined according to actual needs. For example, symmetrical or asymmetrical structures can be used to meet different performance requirements.
[0003] PA6 / PE multi-layer co-extruded composite film has a wide range of applications in the packaging field. For example, due to its good barrier and heat-sealing properties, it is widely used in the packaging of meat, frozen food, and steamed food. In addition, in the pharmaceutical field, PA6 / PE multi-layer co-extruded composite film can be used to produce medical packaging materials such as liquid storage bags and infusion bags to ensure the safety and stability of drugs. Furthermore, PA6 / PE multi-layer co-extruded composite film can also be used for the packaging of electronic products to provide necessary protection and cushioning. With the continuous development of the packaging industry and the improvement of consumers' requirements for packaging quality, PA6 / PE multi-layer co-extruded composite film is developing in the direction of high performance, environmental protection, and multi-function.
[0004] Based on this, Chinese patent CN104943306B discloses a high-strength multi-layer co-extruded biomass composite packaging film, which is obtained by co-extrusion of three layers of film, which are strength layer, adhesive layer and antibacterial layer from top to bottom. The composite film has environmentally friendly raw materials, simple processing, excellent strength and toughness, and good antibacterial effect, and can be used in the field of environmentally friendly packaging films.
[0005] However, the multi-layer co-extruded composite film disclosed in the prior art still has the technical problem of insufficient water resistance. Specifically, as the use conditions of the packaged materials become more and more stringent, the use environment has put forward more stringent requirements on the water resistance, weather resistance and other mechanical properties of the composite film. The core of improving the mechanical properties of the composite film is to improve the material properties of the film itself and to improve the bonding material between the composite films. Among them, adhesives are widely used polymer materials in the modern industrial system. They are involved in printing and dyeing, construction, product packaging, structural sealing and other aspects, and are inseparable from the development of social economy. Moreover, with the continuous improvement and upgrading of relevant technologies in the field of adhesives, different varieties of adhesives have an irreplaceable position in related application fields. They can not only reduce resource waste, reduce budgets, and have good economic applicability; but also facilitate construction, save corresponding manpower and material resources, and have the significance of improving quality and efficiency. During the service life of the adhesive of composite films used in packaging and other fields, it will be affected by the combined effects of temperature, humidity, light, corrosive media and various stresses, and will experience aging phenomena such as gloss change, loss of elasticity, edge cracking, and reduced bonding strength, which will reduce its performance and shorten its effective use time. How to improve its water resistance and other properties is of positive significance. Summary of the invention
[0006] Based on this, it is necessary to provide a high-performance PA6 / PE multi-layer co-extruded composite film adhesive and a preparation method thereof in order to improve the water resistance of the adhesive.
[0007] A high-performance adhesive for PA6 / PE multi-layer co-extruded composite film comprises the following components: polyether diol, diphenylmethane diisocyanate, dimethylol propionic acid, 1,4-butanediol, dibutyltin dilaurate, a silane coupling agent, triethylamine, acetone, nano-calcium carbonate and fumed silica.
[0008] Further, a method for preparing the aforementioned high-performance PA6 / PE multi-layer co-extruded composite film adhesive comprises the following steps: S1: Prepare each material according to the preset ratio; S2: subjecting the polyether diol to a vacuum dehydration treatment; S3: Add the treated polyether diol and diphenylmethane diisocyanate into a reaction kettle equipped with a mechanical stirring device, and react at 80°C for 1.5h under the protection of N2; S4: respectively adding dimethylolpropionic acid, 1,4-butanediol and dibutyltin dilaurate into the reaction kettle; S5: Afterwards, the reaction product in the reactor is sampled every half hour, and the -NCO content thereof is determined by titration; S6: When the -NCO content reaches a preset value, the silane coupling agent is slowly added dropwise to the system, and triethylamine is added for neutralization. At the same time, a preset amount of acetone is added during the reaction to reduce the viscosity of the system. After the reaction continues for at least 1 hour, a silane-modified polyurethane prepolymer is obtained; S7: After subjecting the nano-calcium carbonate and fumed silica to high-temperature dehydration treatment, the prepared silane-modified polyurethane prepolymer, calcium carbonate and fumed silica are mixed and stirred in a preset ratio, dispersed evenly, and then packaged and stored.
[0009] Specifically, in step S1, the proportions of the components are as follows: 40 parts of polyether diol, 13 parts of diphenylmethane diisocyanate, 20 parts of dihydroxymethylpropionic acid, 20 parts of 1,4-butanediol, 2 parts of dibutyltin dilaurate, 3 parts of silane coupling agent, 3 parts of triethylamine, 0.5 parts of acetone, 1.5 parts of nano calcium carbonate and 1.5 parts of fumed silica.
[0010] Specifically, the polyether diol is prepared by mixing PPG 2000 and PPG 400 in a molar ratio of 1:1.
[0011] Specifically, in step S2, the method for vacuum dehydrating the polyether diol is as follows: PPG 2000 and PPG 400 are measured in a molar ratio of 1:1, and the two are placed in a reaction kettle equipped with a stirrer and a thermometer for heating, stirring is started, the temperature is increased and vacuum is drawn, and dehydration is performed at 110° C. to 120° C. and a vacuum degree of 133.3 Pa until no obvious bubbles are generated in the system, indicating that the dehydration is completed; finally, the product is poured into a drying container, filled with nitrogen, sealed and stored for later use.
[0012] Specifically, the silane coupling agent is KH550 or KH560.
[0013] Specifically, in step S5, the preset value of the -NCO content is 18%.
[0014] Specifically, in step S5, the method for determining the content of -NCO is as follows: Weigh 3-5g of the reaction product and add it to a 250mL conical flask, then add 20mL of dry toluene to dissolve the sample; then, transfer 10mL of toluene-di-n-butylamine and add it to the conical flask, place it for 20-30min, then rinse the flask wall with 10mL of anhydrous toluene, then add 40-50mL of isopropanol, drop 3 drops of bromophenol blue indicator, and titrate with standard hydrochloric acid with a concentration of 0.5mol / L; at the same time, make a blank comparison and calculate according to formula 1: Formula 1: wt(NCO)=[(V0-V1)×C×42] / 1000m×100% Wherein, V0 is the amount of hydrochloric acid used in blank titration, V1 is the amount of hydrochloric acid used in sample titration, unit is mL, C is the concentration of hydrochloric acid, unit is mol / L, m is the mass of the sample, and 42 is the molar mass of the isocyanate group.
[0015] Specifically, in the method for determining -NCO, if the content of -NCO at this time is estimated to be less than 5%, the sampling amount of the reaction product is 5-10g.
[0016] In summary, the high-performance PA6 / PE multi-layer co-extruded composite film adhesive of the present invention includes the following components: polyether diol, diphenylmethane diisocyanate, dimethylol propionic acid, 1,4-butanediol, dibutyltin dilaurate, silane coupling agent, triethylamine, acetone, nano calcium carbonate and fumed silica. In addition, the present invention also discloses a method for preparing the aforementioned adhesive, which uses polyether diol and diphenylmethane diisocyanate as main raw materials, dimethylol propionic acid and 1,4-butanediol as chain extenders, and adds a silane coupling agent for modification when -NCO reaches a preset value; under the modification effect, a silane-modified polyurethane prepolymer is first prepared, and then other additives are added according to a preset ratio, thereby preparing a good water-resistant adhesive, and its water absorption rate is significantly reduced compared to existing adhesive products; therefore, the high-performance PA6 / PE multi-layer co-extruded composite film adhesive of the present invention and its preparation method solve the technical problem of how to improve the water resistance of the adhesive. DETAILED DESCRIPTION
[0017] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0018] Specifically, the adhesive for high-performance PA6 / PE multi-layer co-extruded composite film of the present invention includes the following components: polyether diol, diphenylmethane diisocyanate, dihydroxymethylpropionic acid, 1,4-butanediol, dibutyltin dilaurate, silane coupling agent, triethylamine, acetone, nano-calcium carbonate and fumed silica.
[0019] Specifically, in parts by mass, a specific embodiment of the binder for high-performance PA6 / PE multi-layer co-extruded composite film of the present invention is as follows: 40 parts of polyether diol, 13 parts of diphenylmethane diisocyanate, 20 parts of dihydroxymethylpropionic acid, 20 parts of 1,4-butanediol, 2 parts of dibutyltin dilaurate, 3 parts of silane coupling agent, 3 parts of triethylamine, 0.5 parts of acetone, 1.5 parts of nano calcium carbonate and 1.5 parts of fumed silica.
[0020] Specifically, the aforementioned polyether diol is prepared by mixing PPG 2000 and PPG 400 in a molar ratio of 1:1. The specific preparation method is: PPG 2000 and PPG 400 are measured in a molar ratio of 1:1, and the two are placed in a reaction kettle equipped with a stirrer and a thermometer for heating, stirring is started, the temperature is increased and vacuum is drawn, and dehydration is performed under the conditions of 110°C to 120°C and a vacuum degree of 133.3Pa until no obvious bubbles are generated in the system, indicating that the dehydration is completed; finally, the product is poured into a drying container, filled with nitrogen, sealed and stored for later use.
[0021] Specifically, the aforementioned silane coupling agent may be KH550 or KH560.
[0022] Further, a method for preparing the aforementioned high-performance PA6 / PE multi-layer co-extruded composite film adhesive comprises the following steps: S1: Prepare each material according to the preset ratio; S2: subjecting the polyether diol to a vacuum dehydration treatment; S3: Add the treated polyether diol and diphenylmethane diisocyanate into a reaction kettle equipped with a mechanical stirring device, and react at 80°C for 1.5h under the protection of N2; S4: respectively adding dimethylolpropionic acid, 1,4-butanediol and dibutyltin dilaurate into the reaction kettle; S5: Afterwards, the reaction product in the reactor is sampled every half hour, and the -NCO content thereof is determined by titration; S6: When the -NCO content reaches a preset value, the silane coupling agent is slowly added dropwise to the system, and triethylamine is added for neutralization. At the same time, a preset amount of acetone is added during the reaction to reduce the viscosity of the system. After the reaction continues for at least 1 hour, a silane-modified polyurethane prepolymer is obtained; S7: After high-temperature dehydration treatment of nano-calcium carbonate and fumed silica, the prepared silane-modified polyurethane prepolymer, calcium carbonate and fumed silica are mixed, stirred and dispersed evenly according to a preset ratio, and sealed and packaged for storage to obtain the high-performance PA6 / PE multi-layer co-extruded composite film adhesive product of the present invention.
[0023] Specifically, in the aforementioned step S5, the preset value of the -NCO content may be 18%.
[0024] Further, in the aforementioned step S5, the method for determining the content of -NCO is as follows: Weigh 3-5g of the reaction product and add it to a 250mL conical flask, then add 20mL of dry toluene to dissolve the sample; then, transfer 10mL of toluene-di-n-butylamine and add it to the conical flask, place it for 20-30min, then rinse the flask wall with 10mL of anhydrous toluene, then add 40-50mL of isopropanol, drop 3 drops of bromophenol blue indicator, and titrate with standard hydrochloric acid with a concentration of 0.5mol / L; at the same time, make a blank comparison and calculate according to formula 1: Formula 1: wt(NCO)=[(V0-V1)×C×42] / 1000m×100% Wherein, V0 is the amount of hydrochloric acid used in blank titration, V1 is the amount of hydrochloric acid used in sample titration, unit is mL, C is the concentration of hydrochloric acid, unit is mol / L, m is the mass of the sample, and 42 is the molar mass of the isocyanate group.
[0025] In the aforementioned method for determining -NCO, if the content of -NCO at this time is estimated to be less than 5%, the sampling amount of the reaction product is 5-10g.
[0026] Specifically, the curing process of silane-modified polyurethane is as follows: the segment silane alkoxy undergoes hydrolysis reaction to generate S-OH, and alcohols are generated at the same time; then, Si-OH and Si-OH undergo dehydration condensation to form a network cross-linked structure of Si-O-Si bonds, and the cross-linked structure of the polyurethane segment is formed between these Si-O-Si cross-linking points. The definition of the surface drying time of the adhesive refers to the time when the adhesive is contacted with the adhesive by a polyethylene film during the curing process, and when there is no residual adhesive adhering to its surface, this time is the surface drying time. In the aforementioned embodiments of the present invention, the component contents of the silane coupling agent are defined as: 1 part, 2 parts, 3 parts, 4 parts and 5 parts, respectively, and the surface drying time is measured respectively. It can be seen that the data of the surface drying time are: 3.3h, 2.8h, 1.5h, 1.2h and 0.9h, respectively. That is, with the increase of the content of the silane coupling agent, the surface drying time of the silane-modified polyurethane adhesive is gradually reduced. Since the alkoxy groups in silane can react with water molecules in the air to crosslink and cure, as the silane content increases, that is, the silane alkoxy groups in the reaction system increase, the above reaction is accelerated, so its surface drying time is gradually reduced. Therefore, it is believed that the greater the amount of silane coupling agent used, the more conducive to its surface drying efficiency.
[0027] Further, the test method for water resistance is as follows: The adhesive sample to be tested is dried under vacuum conditions for 24 hours, and then the mass W1 of the adhesive sample film is measured at room temperature. Next, the adhesive sample film is immersed in deionized water at room temperature, taken out after 24 hours, and the water on the surface of the adhesive sample is absorbed and then its mass W2 is weighed. Based on the difference in mass before and after, its water absorption rate Ω is calculated according to formula 2: Ω=(W1-W2) / W1×100%.
[0028] Similarly, the component contents of silane coupling agent are defined as: 1 part, 2 parts, 3 parts, 4 parts and 5 parts, and their water resistance is measured respectively. It can be seen that the water absorption data are: 13%, 9%, 6%, 7% and 7.5% respectively. It can be seen that with the increase of silane coupling agent content, the water absorption rate of adhesive generally shows a downward trend; and when the content of silane coupling agent increases to a certain extent, the water absorption rate of adhesive increases slightly. This is because when the silane content is within a low range, as its content increases, a cross-linking structure is generated in the system, and the stability increases, so the water absorption rate of the adhesive decreases; when the content of silane coupling agent is high, the cross-linking structure in the system increases, and its local cross-linking is excessive, which reduces the stability of the system; therefore, its water absorption rate increases slightly.
[0029] The commercially available adhesive is taken as comparative example 1, and the aforementioned embodiment is taken as embodiment 1. The water resistance of the two is compared and tested. It can be seen that the water absorption rate of comparative example 1 is 18%, while the water absorption rate of embodiment 1 is 6%. It can be seen that the water resistance performance of the adhesive prepared according to the formula and preparation method proposed in the present invention is significantly improved.
[0030] In summary, the high-performance PA6 / PE multi-layer co-extruded composite film adhesive of the present invention includes the following components: polyether diol, diphenylmethane diisocyanate, dimethylol propionic acid, 1,4-butanediol, dibutyltin dilaurate, silane coupling agent, triethylamine, acetone, nano calcium carbonate and fumed silica. In addition, the present invention also discloses a method for preparing the aforementioned adhesive, which uses polyether diol and diphenylmethane diisocyanate as main raw materials, dimethylol propionic acid and 1,4-butanediol as chain extenders, and adds a silane coupling agent for modification when -NCO reaches a preset value; under the modification effect, a silane-modified polyurethane prepolymer is first prepared, and then other additives are added according to a preset ratio, thereby preparing a good water-resistant adhesive, and its water absorption rate is significantly reduced compared to existing adhesive products; therefore, the high-performance PA6 / PE multi-layer co-extruded composite film adhesive of the present invention and its preparation method solve the technical problem of how to improve the water resistance of the adhesive.
[0031] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0032] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A high-performance PA6 / PE multi-layer co-extruded composite film adhesive, characterized in that: The invention comprises the following components: polyether diol, diphenylmethane diisocyanate, dimethylol propionic acid, 1,4-butanediol, dibutyltin dilaurate, a silane coupling agent, triethylamine, acetone, nano calcium carbonate and gas phase silicon dioxide.
2. A method for preparing a high-performance PA6 / PE multi-layer co-extruded composite film binder as claimed in claim 1, characterized in that: It includes the following steps: S1: Prepare each material according to the preset ratio; S2: subjecting the polyether diol to a vacuum dehydration treatment; S3: Add the treated polyether diol and diphenylmethane diisocyanate into a reaction kettle equipped with a mechanical stirring device, and react at 80°C for 1.5h under the protection of N2; S4: respectively adding dimethylolpropionic acid, 1,4-butanediol and dibutyltin dilaurate into the reaction kettle; S5: Afterwards, the reaction product in the reactor is sampled every half hour, and the -NCO content thereof is determined by titration; S6: When the -NCO content reaches a preset value, the silane coupling agent is slowly added dropwise to the system, and triethylamine is added for neutralization. At the same time, a preset amount of acetone is added during the reaction to reduce the viscosity of the system. After the reaction continues for at least 1 hour, a silane-modified polyurethane prepolymer is obtained; S7: After subjecting the nano-calcium carbonate and fumed silica to high-temperature dehydration treatment, the prepared silane-modified polyurethane prepolymer, calcium carbonate and fumed silica are mixed and stirred in a preset ratio, dispersed evenly, and then packaged and stored.
3. The method for preparing a high-performance PA6 / PE multi-layer co-extruded composite film binder according to claim 2, characterized in that: In step S1, the proportions of the components are as follows: 40 parts of polyether diol, 13 parts of diphenylmethane diisocyanate, 20 parts of dihydroxymethylpropionic acid, 20 parts of 1,4-butanediol, 2 parts of dibutyltin dilaurate, 3 parts of silane coupling agent, 3 parts of triethylamine, 0.5 parts of acetone, 1.5 parts of nano calcium carbonate and 1.5 parts of fumed silica.
4. The method for preparing a high-performance PA6 / PE multi-layer co-extruded composite film binder according to claim 2, characterized in that: The polyether diol is prepared by mixing PPG 2000 and PPG 400 in a molar ratio of 1:
1.
5. The method for preparing a high-performance PA6 / PE multi-layer co-extruded composite film binder according to claim 4, characterized in that: In step S2, the method for vacuum dehydrating the polyether diol is as follows: PPG 2000 and PPG 400 are measured in a molar ratio of 1:1, and the two are placed in a reaction kettle equipped with a stirrer and a thermometer for heating, stirring is started, the temperature is increased and vacuum is drawn, and dehydration is performed at 110° C. to 120° C. and a vacuum degree of 133.3 Pa until no obvious bubbles are generated in the system, indicating that the dehydration is completed; finally, the product is poured into a drying container, filled with nitrogen, sealed and stored for later use.
6. The method for preparing a high-performance PA6 / PE multi-layer co-extruded composite film binder according to claim 2, characterized in that: The silane coupling agent is KH550 or KH560.
7. The method for preparing a high-performance PA6 / PE multi-layer co-extruded composite film binder according to claim 2, characterized in that: In step S5, the preset value of the -NCO content is 18%.
8. The method for preparing a high-performance PA6 / PE multi-layer co-extruded composite film binder according to claim 2, characterized in that: In step S5, the method for determining the content of -NCO is as follows: Weigh 3-5g of the reaction product and add it to a 250mL conical flask, then add 20mL of dry toluene to dissolve the sample; then, transfer 10mL of toluene-di-n-butylamine and add it to the conical flask, place it for 20-30min, then rinse the flask wall with 10mL of anhydrous toluene, then add 40-50mL of isopropanol, drop 3 drops of bromophenol blue indicator, and titrate with standard hydrochloric acid with a concentration of 0.5mol / L; at the same time, make a blank comparison and calculate according to formula 1: Formula 1: wt(NCO)=[(V0-V1)×C×42] / 1000m×100% Wherein, V0 is the amount of hydrochloric acid used in blank titration, V1 is the amount of hydrochloric acid used in sample titration, unit is mL, C is the concentration of hydrochloric acid, unit is mol / L, m is the mass of the sample, and 42 is the molar mass of the isocyanate group.
9. The method for preparing a high-performance PA6 / PE multi-layer co-extruded composite film binder according to claim 8, characterized in that: In the method for determining -NCO, if the content of -NCO at this time is estimated to be less than 5%, the sampling amount of the reaction product is 5-10g.
Citation Information
Patent Citations
A high-strength multilayer co-extruded biomass composite packaging film
CN104943306B